2004
DOI: 10.1007/s10151-004-0172-3
|View full text |Cite
|
Sign up to set email alerts
|

Colonic neoplastic polyps: biopsy is not efficient to exclude malignancy. The Trafford experience

Abstract: The biological behaviour of the polyp depends entirely on its histological subtype. Adenomas are the classic precursors to carcinoma. Polyp biopsy can differentiate neoplastic (adenoma and carcinoma) from non-neoplastic polyps (hyperplastic, inflammatory, hamartomatous). Due to potential sampling error, biopsy does not always differentiate between adenoma and carcinoma. Our aim was to investigate the degree of this potential sampling error. We carried out a study to compare the results of biopsies vs. total ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 28 publications
1
19
0
1
Order By: Relevance
“…10 the risk here is that the excision will not prove curative and, above all, an accurate histological diagnosis of the lesion may not be obtained. 11 in our experience, 12,13 the percentage of invasive adenocarcinomas among rectal adenomas is high. We therefore advocate total excision of the wall for all rectal tumors that can be treated with local surgery.…”
Section: Transanal Endoscopic Surgery With Total Wall Excision Is Reqmentioning
confidence: 86%
“…10 the risk here is that the excision will not prove curative and, above all, an accurate histological diagnosis of the lesion may not be obtained. 11 in our experience, 12,13 the percentage of invasive adenocarcinomas among rectal adenomas is high. We therefore advocate total excision of the wall for all rectal tumors that can be treated with local surgery.…”
Section: Transanal Endoscopic Surgery With Total Wall Excision Is Reqmentioning
confidence: 86%
“…It has been shown that when making a diagnosis of malignancy in an adenoma following a biopsy a false-negative rate of 18.5% occurs when compared to examining the entire specimen [21]. Therefore it is important to realise that, to make a definitive diagnosis of an adenoma and rule out malignancy, the pathologist must look at the entire specimen.…”
Section: Diagnosing the Malignant Adenomamentioning
confidence: 99%
“…Several studies have shown that the rate of adenocarcinoma in adenomas in biopsies is underestimated when compared with later total polypectomy (15,16). The excision margins have also been discussed.…”
Section: Introductionmentioning
confidence: 99%